Leakage current suppression in spatially controlled Si-doped ZrO2 for capacitors using atomic layer deposition - Lee, Kunyoung; Jang, Woochool; Kim, Hyunjung; Lim, Heewoo; Kim, Bumsik; Seo, Hyungtak; Jeon, Hyeongtag (Thin Solid Films, 2018)
Among various high-k materials, zirconium dioxide (ZrO2) has attracted considerable attention due to its high dielectric constant and wide band gap. However, its main disadvantage of ZrO2 films which have tetragonal phase is its large leakage current along grain boundaries. Doping ZrO2 with silicon has been proposed as a solution to this issue. In this study, we investigated the electronic structure of Si-doped ZrO2 thin films. We used atomic layer deposition to deposit Si-doped ZrO2 thin films. This method has many advantages such as excellent step coverage, low process temperature, and ultrathin growth. We found that proper Si doping, which affects Si distribution in the ZrO2 and therefore its electronic band structure, is necessary for leakage current reduction.
Keywords: Electronic band structure; High dielectric constants; High-k materials; Leakage current reduction; Low process temperature; MIM capacitors; Zirconium dioxide; ZrO2; Atomic layer deposition; High-k material; MIM capacitor; ZrO2